The Effect of a Station-Based Chip Shot Learning Model Using a No. 9 Iron on Golf Learning Outcomes - Aep Rohendi (STKIP Pasundan, 2026)
This study aimed to examine the effect of a station-based chip shot learning model using a No. 9 iron on students' golf learning outcomes. The study was redesigned as a quasi-experimental study using a posttest-only control group design. The participants consisted of 36 students at Efro Golf Academy Bandung. Data were collected using a chip shot performance test and analyzed through descriptive statistics and an independent samples t-test at a significance level of 0.05. The results showed with independent samples t-test indicated a statistically significant difference between the two groups, t(34) = 15.84, p < .001, with a very large effect size. These findings indicate that the station-based chip shot learning model using a No. 9 iron was more effective than conventional instruction in improving students' chip shot skills in golf learning.